2023
DOI: 10.1007/s42495-022-00102-8
|View full text |Cite
|
Sign up to set email alerts
|

Do unilateral trade preferences help reduce poverty in beneficiary countries?

Abstract: This paper has investigated the utilization of non-reciprocal (or unilateral) trade preferences (NRTPs) provided by QUAD countries on poverty in recipient-countries. It uses a panel dataset of 77 beneficiaries of NRTPs over the period of 2002-2019, and considers two main blocks of NRTPs, namely 'Generalized System of Preferences' (GSP) programs and 'other trade preferences programs'. The analysis relies on two main indicators of poverty, i.e., the poverty headcount ratio at $1.90 and the poverty gap at $1.90, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 168 publications
0
2
0
Order By: Relevance
“…Santos‐Paulino (2017) has reported empirical evidence that while the export of manufactured products by developing countries has been associated with poverty reduction, in low‐income countries, it is rather the export of agricultural products that helps reduce poverty. Gnangnon (2023a) has found that non‐reciprocal trade preferences have contributed to poverty reduction in beneficiary (developing) countries, with a larger poverty reduction effect taking place in the least developed countries (LDCs).…”
Section: Theoretical Discussion On the Effect Of Export Product Quali...mentioning
confidence: 99%
“…Santos‐Paulino (2017) has reported empirical evidence that while the export of manufactured products by developing countries has been associated with poverty reduction, in low‐income countries, it is rather the export of agricultural products that helps reduce poverty. Gnangnon (2023a) has found that non‐reciprocal trade preferences have contributed to poverty reduction in beneficiary (developing) countries, with a larger poverty reduction effect taking place in the least developed countries (LDCs).…”
Section: Theoretical Discussion On the Effect Of Export Product Quali...mentioning
confidence: 99%
“…Gnangnon (2023) investigated how unilateral trade preferences impact the poverty levels of beneficiary nations. The study focused on QUAD, Quadrilateral Security Dialogue (QSD), an informal strategic alliance comprising the United States of America (USA), India, Australia, and Japan with the principal aim of facilitating the development of a free, open, prosperous, and inclusive Indo‐Pacific region.…”
Section: Literature Reviewmentioning
confidence: 99%